Knowing your halal food ingredients (adulteration and istihalah) - Jamaludin, Mohammad Aizat (2019)
1. Quran on Halalan Tayyiban 2. Principles of Halal due to Adulteration 3. Classification of Haram Materials in Quran 4. What is Adulteration? 5. Issues on Adulteration 6. Alternative Reference Sources in Determination of Halal and Haram 7. What is Istihalah? 8. Component in Istihalah 9. The School of Thought Regarding Istihalah Application of Istihalah in Alcohol and Gelatin Products Conclusion